Therapeutic monitoring of isoniazid, pyrazinamide and rifampicin in tuberculosis patients using LC - (:unkn) unknown (SPRINGER HEIDELBERG, 2005)
The objective of this study was to measure plasma concentration of isoniazide (INH), pyrazinamide (PZA) and rifampisin (RIF) in tuberculosis patients by using HPLC. 100 mu L of plasma was deproteinized by adding trichloroacetic acid and acetonitrile to yield INH, PZA and RIF respectively. They were analysed by HPLC using a reversed phase C-18 pre-column linked to a 4 mu m C-18 analytical column with a gradient solvent programme, which delivered 3% to 40% (v/v) acetonitrile in phosphate buffer in 20 min at rate of 0.8 mL min(-1). Signals were monitored by diode-array detector. Acetanilide was used as internal standard. The method is reproducible and accurate with lower limits of quantification of 0.6 mg L-1 for INH, 1.5 mg L-1 for PZA and 0.7 mg L-1 for RIF. The plasma of 25 patients receiving daily standard therapy were assayed for INH, PZA and RIF 3 h after administration. Plasma concentration were found between 0.98 and 6.27 mg L-1 for INH, 11.05 and 47.26 mg L-1 for PZA, 5.09 and 33.20 mg L-1 for RIF respectively. Many of the plasma levels were found to be sub therapeutic. This practical method may be used for monitoring drug plasma levels of patients who fail to respond to treatment.
Keywords: column liquid chromatography; therapeutic drug monitoring; isoniazid; tuberculosis treatment; pyrazinamide and rifampicin; LIQUID-CHROMATOGRAPHIC DETERMINATION; BRONCHOALVEOLAR LAVAGE; HUMAN PLASMA; METABOLITES; FLUID; ASSAY